PTH-108 Predictors of complications after hpb resections. (22nd June 2015) - Ellis, J
Abstract : Introduction: To identify factors which may predict an increased risk of peri-operative complication in the first 48 h post HPB resection. Method: Retrospective data collected on 1057 patients who underwent liver or pancreas resection at a single centre between Jan 2011 and Nov 2014 using local database and reporting system. Complications were graded according to the Clavien-Dindo classification (severe – grade I–II, minor III–V). Results: 801 patients underwent liver resection (major 535, minor 266) with 48 h complication rate of 6.7% (and 25.8% rate within 30 days). Severe complications were associated with increased length of stay on ITU from 1 day (no complication) to 10 days. A number of statistically significant factors were associated with increased risk of complication (age, indication, transfusion, operation time, NorAdrenaline requirement). Multivariable analysis of these factors demonstrated that only Creatinine had any predictive value with post-op day 1 levels of 66.1 (no complication), 76.3 (minor) and 92.2µmol/l (severe). Severe complications had a +9.1% mean rise in Creatinine from pre-op to post-op day 1 (no complications had a fall of -14.5%). ROC curve analysis resulted in an AUROC of 0.65 (p < 0.001) for Creatinine-related factors. 236 patients underwent a Whipples procedure (PPPD or Classical) with a complication rate of 11.3% within 48 h (46.5% within 30 days). Again, severe complications were associated with increased length of stay on ITU (8 days in this group compared to 2 days for no complications). In contrast to the liver data, the only factors with statistical significance associated with severe complications were Creatinine-related. Creatinine levels of 67.3, 79.9 and 82.6µmol/l and changes in Creatinine of -4.5%, +6.0% and +25.4% in the no, minor and severe complication groups respectively were observed. The AUROC was 0.66 (pre-op Creatinine) and 0.7 (change in Creatinine). Conclusion: Multivariable analysis demonstrated that the only factors predictive of complication in this group of patients were pre-op Creatinine and change in Creatinine. With a low PPV (13.1% and 25.4% for liver and pancreas group respectively) this is not however reliable in identifying patients at risk of all complications, though a sensitivity of 90.0% and 72.7% for severe risk patients does add some value. Most notably the negative predictive value for these tests is >93% for all groups and therefore has reasonable predictive value in identifying patients unlikely to encounter a peri-operative complication. This study demonstrates the difficulty in predicting which patients are at risk of post-operative complications and also provides some novel data on the use of Creatinine as a potential marker of risk. Disclosure of interest: None Declared.